1981
DOI: 10.1139/o81-069
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of muscle glycolytic enzymes with thin filament proteins

Abstract: Purified glycolytic enzymes were individually chromatographed through columns of Sepharose 4B containing a covalently bound F-actin-tropomyosin complex. Five of these enzymes, aldolase, glyceraldehyde-phosphate dehydrogenase, lactate dehydrogenase, pyruvate kinase, and phosphoglycerate kinase were able to interact with the complex. Glucosephosphate isomerase, triosephosphate isomerase, phosphoglycerate phosphomutase, and enolase did not bind to the F-actin-tropomyosin matrix. One nonbinding enzyme, phosphoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 0 publications
3
56
0
Order By: Relevance
“…Numerous studies have demonstrated interactions between the cytoskeleton and glycolytic enzymes, especially GAPDH, aldolase and PK. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] In this study, quantities of these glycolytic enzymes, as well as actin, tubulin and tropomyosin, were sufficient in U87 pseudopodia to be detected with Figure 4 DeCyder ratios Coomassie blue staining, thus establishing the potential for the energy-generating portion of the glycolytic pathway to energize cytoskeletal proteins for migration within U87 pseudopodia. Polymerization of actin and tubulin shares a similar use of energy from nucleotide triphosphate hydrolysis.…”
mentioning
confidence: 63%
“…Numerous studies have demonstrated interactions between the cytoskeleton and glycolytic enzymes, especially GAPDH, aldolase and PK. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] In this study, quantities of these glycolytic enzymes, as well as actin, tubulin and tropomyosin, were sufficient in U87 pseudopodia to be detected with Figure 4 DeCyder ratios Coomassie blue staining, thus establishing the potential for the energy-generating portion of the glycolytic pathway to energize cytoskeletal proteins for migration within U87 pseudopodia. Polymerization of actin and tubulin shares a similar use of energy from nucleotide triphosphate hydrolysis.…”
mentioning
confidence: 63%
“…Aldolase interacts with calmodulin (20,75) and phospholipase D 2 (21) and therefore may modulate signal transduction pathways. Aldolase is also an actin-binding protein that exhibits a dynamic interaction with the cytoskeleton (22,23). Importantly, aldolase interacts with the H Ï© -ATPase (25,26) and GLUT4 (27), two proteins regulated by intracellular trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Aldolase Binding Reduces NKCC2 Surface Expression-Aldolase is a protein associated with the actin cytoskeleton and can cross-link actin fibers (22,23). Because actin cytoskeleton has been implicated in the regulation of Na-K-Cl co-transport in mouse kidney cultured TAL cells (58), we therefore sought to study the effect of aldolase binding on NKCC2 surface expression.…”
Section: Endogenous Aldolase Protein Interacts and Co-localizes With mentioning
confidence: 99%
“…The choice of a 0.05M ionic strength is in accordance with a variety of experimental investigations. [2][3][4] This choice also enhanced the interaction making it easier to observe statistically. The 0.05M ionic strength increased the number of bimolecular complexes and allowed for a better visualization of the electrostatic field.…”
Section: Charge Assignments and Epsmentioning
confidence: 99%
“…For example, the glycolytic enzymes fructose-1,6-bisphosphate aldolase (aldolase) and glyceraldehyde-3-phosphate dehydrogenase (GADPH)) have been shown to interact with cytoskeletal proteins, especially F-actin in human, 1 rabbit, 2 fish, 3 and possibly Drosophila. 4 These interactions have been studied by a variety of experimental methods such as affinity chromatography, 2 histochemical observations, 3 copelleting, 5 and co-electrophoresis. 6 These interactions have been postulated to be electrostatic in nature due to their dependence on pH, ionic strength, monovalent (K + , Na + ) or divalent (Ca 2+ , Mg 2+ ) cations, as well as metabolites (ATP, ADP).…”
mentioning
confidence: 99%